Automatic generation of ontologies from business process models - Figueiredo, Lukas Riehl [UNESP]; De Oliveira, Hilda Carvalho [UNESP] (My University, 2018)
Business process models are used in organizational environments for a better understanding of the interactions between the different sectors and the interdependencies between processes. However, business process models may present legibility problems and navigation difficulties as they become extensive. The representation of implicit knowledge is complex, as well as the interdependencies are not always easy to be understood. The use of ontologies has opened a complementary perspective to provide processes with machine-accessible semantics. Ontologies contribute to the conceptualization and organization of the embedded and unstructured information that is present in the business processes and that must be explored. The ontologies are used to structure the implicit knowledge that is present in the business processes, allowing the understanding by machine. They also facilitate the sharing and reusing of knowledge by various agents, human or artificial. In this context, this work presents a systematic process to generate an ontology from a business process model in BPMN, allowing to query information about the model. For this, the PM2ONTO tool was developed, aiming to generate the ontology in OWL automatically and to provide predefined queries, elaborated with SPARQL.
Keywords: BPMN; Business process model; Ontology; OWL; SPARQL; XPDL